Productivity of Boran cattle maintained with chemoprophylaxis under high tsetse challenge at Mkwaja ranch in Tanzania. 2. Productivity - Trail, J.C.M.; Murray, M.; Sones, Keith R.; Jibbo, J.M.C.; Durkin, J.W.; Light, D.E. (OAU/STRC, 1985)
Reports the viability, reproduction and associated growth rates achieved by grade Boran cattle maintained by chemoprophylaxis under high tsetse challenge at Mkwaja Ranch in Tanzania, W., particularly emphasis on calving interval, pre-weaning mortality, pre-weaning growth and the resultant cow productivity.